Spectrophotometric Determination of Mesalazine Based on Schiff Base ‎Formation with 2,4-dimethoxybenzaldehyde and 3,4-dihydroxybenzaldehyde. - Rasul Jameel Ali (Zanco Journal of Pure and Applied Sciences, 2023)
Two straightforward, fast, easy, accurate, and sensitive spectrophotometric methods were developed to measure mesalazine either in its pure form or in tablet dosage form The proposed procedures, specifically, rely on a condensation reaction between mesalazine and aromatic aldehydes, (method A) and (method B), to produce yellow color Schiff's bases. For methods A and B, the concentration ranges where Beer's relationship was observed were 0.4–10 µg mL-1 with a limit of detection of 0.1070 µg mL-1 and a limit of quantification of 0.1323 µg mL-1, and 2–15 µg mL–1 with a limit of detection of 0.3244 µg mL–1 and 0.4010 µg mL–1, respectively. The recovery percentage was 97.82% to 102.1% and 98.15% to 99.91% for the two proposed methods. The proposed methods have been used successfully to determine mesalazine in their tablet formulations.